PEMBENTUKAN KARAKTER DISIPLIN MELALUI PENDIDIKAN BERBASIS INTRAKURIKULER KELAS IV MI UWAYS AL QORNI PEKANBARU - Humaysah; Sakban; Salman; Rahmi (Jurnal Payung Sekaki : Kajian Keislaman, 2025)
This study aims to describe the development of disciplinary character through intraculicular-based educational activities in Grade IV at MI Uways Al Qorni Pekanbaru. The primary focus of this research is the implementation of daily religious activities, namely congregational Duha prayer, morning dhikr, and collective recitation of daily prayers. This research employs a descriptive qualitative approach, with data collected through observation, interviews, and documentation. The findings indicate that these intraculicular activities are consistently carried out every morning before the start of the learning process, which positively contributes to the formation of students’ discipline. Students become more organized in managing their time, develop self-awareness in fulfilling their obligations, and demonstrate responsibility and perseverance in following school rules. Thus, the implementation of integrated religious activities within the intraculicular program proves effective in instilling disciplinary values from an early age.